Power, Alliances, and Redistribution The Politics of Social Protection for Low-Income Earners in Argentina, 1943-2015 - Bossert, Carl Friedrich (Verlag Barbara Budrich, 2021)
Latin America is considered the most unequal continent in the world. Paradoxically, the development of resource-intensive social systems has done little to change the social imbalance. The author traces this paradox using Argentina as an example, uncovering the underlying conflicts of power and interests, and identifying successful strategies for implementing inclusive policies. As the first study of its kind, it systematically examines the long-term development of social security for low-income earners in Argentina and analyzes the decisive political, social, and economic factors influencing it.